2020
DOI: 10.1001/jamanetworkopen.2020.19452
|View full text |Cite|
|
Sign up to set email alerts
|

Yield and Utility of Germline Testing Following Tumor Sequencing in Patients With Cancer

Abstract: IMPORTANCE Both germline genetic testing and tumor DNA sequencing are increasingly used in cancer care. The indications for testing and utility of these 2 tests differ, and guidelines recommend that germline analysis follow tumor sequencing in certain patients to determine whether particular variants are of somatic or germline origin. Broad clinical experience with such follow-up testing has not yet been thoroughly described. OBJECTIVE To examine the yield and utility of germline testing following tumor DNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 21 publications
1
95
3
1
Order By: Relevance
“…In 2020, a Harvard webinar 18 described digital health technologies as a "pillar" upon which healthcare would be built and showed how growth was accelerating in the midst of the COVID pandemic. On another common healthcare front, a recent paper from Lincoln et al 19 reported that tumor tissue genome sequencing coupled with blood tests for germline mutations reveals higher than expected impacts of inherited contributions to a variety of common cancers. Such developments coupled with the growing number of gene arrays now being marketed directly to consumers 4 exemplify the importance of familiarizing medical students with the basics behind AI and genomics in precision medicine 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, a Harvard webinar 18 described digital health technologies as a "pillar" upon which healthcare would be built and showed how growth was accelerating in the midst of the COVID pandemic. On another common healthcare front, a recent paper from Lincoln et al 19 reported that tumor tissue genome sequencing coupled with blood tests for germline mutations reveals higher than expected impacts of inherited contributions to a variety of common cancers. Such developments coupled with the growing number of gene arrays now being marketed directly to consumers 4 exemplify the importance of familiarizing medical students with the basics behind AI and genomics in precision medicine 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, negative tumor-only testing is not an adequate surrogate for dedicated germline testing, especially when the implications for cancer surveillance, treatment, and cascade testing are so critical. As recently shown by Lincoln et al, 17 Tumor result Germline and somatic results because of the technical limitations of tumor sequencing, variant interpretation differences, or differences in the genes tested in the tumor versus the germline. Perhaps most importantly, in tumor-only testing, the germline nature of findings may be misinterpreted by providers inexperienced in cancer genetics or incorrectly relayed to patients, resulting in suboptimal care not only for the patient but also for at-risk family members.…”
Section: Tumor-only Versus Parallel Tumor-normal Testingmentioning
confidence: 99%
“…In many settings, genetic counseling and testing occur only after a major health event, such as sudden cardiac arrest, late‐stage ovarian cancer, or unexplained seizures in children. Long diagnostic odysseys, second primary cancers (Lincoln et al, 2020), or multiple affected family members are too often the norm before genetics is considered as part of a differential diagnosis, if at all. This lack of consistency leads to disparate use of genetics within healthcare, rather than an integrated approach.…”
Section: Genetics In Healthcare: Yesterday and Todaymentioning
confidence: 99%